Differential Expression of Genes in the Cornea compared to the Optic Nerve - Haji Molla Hoseyni , Behnaz; Pournoor, Ehsan (Journal of Ophthalmic and Optometric Sciences, 2020)
Abstract Background: Identification of tissue-specific biomarkers can help us in finding the causes of disease. In this context, finding genes that are expressed in different tissues gives us guidance in cell differentiation. Material and Methods: we examined genes with different expressions in both optic nerve and corneal tissues. First, we found differentially expressed genes on a dataset including 4 corneal and 4 optic nerve samples, then evaluated them on another independent dataset to validate the findings. Finally, we performed Enrichment Analysis and Network Evaluation of the obtained DEGs. Results: we gained 6 genes that are highly expressed in the optic nerve than the cornea and 99 genes with higher expression in the cornea than in the optic nerve. Conclusion: We saw traces of DEGs in the mechanism of action of the corresponding cells. In this study, we did not use the FDR method and thus we do not have false positive in final DEGs. Keywords: Biomarker Discovery; Cornea; Optic Nerve; Differential Gene Expression Analysis.